Lie, cheat, and steel : governance and scandal at ThyssenKrupp - Shein, James B., 1942-; Meagher, Evan (London : Kellogg School of Management, 2017)
Hiesinger had been CEO since 2010. Early in his tenure, ThyssenKrupp incurred massive losses from disastrous steel investments and faced allegations of colluding with other companies to fix prices in its railway steel operations. As a result, Hiesinger had been forced to dismiss three executive board members, one for violating company policy. After a supervisory board member also was dismissed for violating company policy, the company's offices were raided in an investigation of price-fixing in steel contracts to the automotive industry.Cromme had been sharply criticized by shareholders and analysts as an impediment to the cultural, strategic, and governance changes Hiesinger was trying to make to address the scandals at ThyssenKrupp, but for months he defiantly had resisted calls for his removal. With no warning, he resigned without naming a successor or creating a plan to select one.Now that he no longer needed to deal with the distractions created by Cromme's presence, Hiesinger was free to finalize a plan to address the defects in ThyssenKrupp's governance.
Originally published in Shein, J. B., & Meagher, E. (2017). Lie, cheat, and steel: Governance and scandal at ThyssenKrupp. 5-117-001. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Thyssen Krupp AG -- Management; Industrial management; Strategic planning; Corporations -- Corrupt practices; Steel industry and trade